Автоматизированное формирование расчетных моделей турбогенераторов для программной среды FEMM - Милых, Владимир Иванович; Полякова, Наталия Владимировна (НТУ "ХПИ", 2015)
Представлены принципы автоматизированного формирования графической и физической моделей турбогенераторов на алгоритмическом языке Lua для расчета их магнитных полей и параметров в программной среде пакета FEMM. Возможности составленного скрипта Lua демонстрируются на примере реального турбогенератора.

Attention is paid to the popular FEMM (Finite Element Method Magnetics) program which is effective in the numerical calculations of the magnetic fields of electrical machines. The main problem of its using - high costs in time on the formation of a graphical model representing the design and on the formation of the physical model representing the materials properties and the winding currents of machines – is solved. For this purpose, principles of the automated formation of such models are developed and presented on the turbogenerator example. The task is performed by a program written in an algorithmic language Lua integrated into the package FEMM. The program is universal in terms of varying the geometry and dimensions of the designed turbogenerators. It uses a minimum of input information in a digital form representing the design of the whole turbogenerator and its fragments. A general structure of the Lua script is provided, significant parts of its text, the graphic results of work's phases, as well as explanations of the program and instructions for its use are given. Performance capabilities of the compiled Lua script are shown on the example of the real 340 MW turbogenerator.
Automated formation of calculation models of turbogenerators for software environment FEMM
Keywords: расчеты магнитных полей; программа FEMM; метод конечных элементов; турбогенераторы; автоматизированное формирование; Lua скрипт; program FEMM; Finite Element Method; turbogenerator; automated formation; Lua script